Prolanis Exercise to Reduce Blood Sugar and High Blood Pressure in the Elderly at the Gunungpati Community Health Center: Prolanis Exercise to Reduce Blood Sugar and High Blood Pressure in the Elderly at the Gunungpati Community Health Center - Ratnasari Ratnasari; Dhimas Eka Prayoga; Elva Dwi Yuliyani; Ersa Novita Andriyani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Diabetes mellitus and hypertension are chronic diseases that often cause serious complications such as stroke, so they require proper treatment. The Chronic Disease Management Program (Prolanis) aims to improve the quality of life of sufferers through a proactive approach, including providing exercise for prolanis participants. This study aims to analyze the application of prolanis exercise on reducing blood sugar and blood pressure in the elderly at the Gunungpati Health Center in Semarang. The study used a quasi-experimental method with a one-group pre-post-test design. A sample of 60 elderly people participated in prolanis activities, 30 elderly people with diabetes mellitus and 30 elderly people with hypertension. The activity was carried out by measuring blood sugar and blood pressure (pre-test), then given prolanis exercise intervention for 10 minutes, after the intervention the participants' blood sugar and blood pressure were measured (post-test). Data analysis for diabetes mellitus used a dependent t-test and hypertension used a Wilcoxon test. The results of the Dependent t-test showed the effect of prolanis exercise on lowering blood sugar with a p value = 0.024. The results of the Wilcoxon test showed the effect of Prolanis gymnastics on lowering blood pressure with a p value = 0.000. This activity shows that Prolanis gymnastics is effective in managing hypertension and diabetes mellitus in the elderly.